Long repetition time experiments for measurement of concentrations in systems with chemical exchange and undergoing temporal variation–comparison of methods with and without correction for saturation - Galbán, Craig J; Spencer, Richard G.S (Journal of magnetic resonance (1997), 2003)
The purpose of this paper is to compare two methods for quantifying metabolite concentrations using the one-pulse experiment for a sample undergoing chemical exchange and subject to an intervention or other temporal variation. The methods, LATR-C (Long Acquisition TR (interpulse delay); Corrected for partial saturation) and LATR-NC (Long Acquisition TR; Not Corrected), are compared in terms of signal-to-noise ratio, SNR, per unit time and quantitation errors. Parameters relevant to the isolated perfused rat heart are used as a specific application, although the results are general. We assume throughout that spin–lattice relaxation times, T 1, do not change. For a given flip angle, θ, TR’s are calculated which result in maximal SNR per unit time under 10%, 5%, and 1% constraints on quantitation errors. Additional simulations were performed to demonstrate explicitly the dependence of the quantitation errors on TR for a fixed θ. We find (i) if the allowed error is large, and when both metabolite concentrations and rate constants vary, LATR-C permits use of shorter TR, and hence yields greater SNR per unit time, than LATR-NC; (ii) for small allowed error, the two methods give similar TR’s and SNR per unit time, so that the simpler LATR-NC experiment may be preferred; (iii) large values of θ result in similar constrained TR’s and hence SNR per unit time for the two methods; (iv) the ratio of concentrations of metabolites with similar T 1 exhibit similar errors for the two methods.